Marine and freshwater fishes of Alabama: a revised checklist and discussion of taxonomic issues - Bagley, Justin C.; Johnson, Cal C.; Mcgregor, Stuart W.; Breitman, Maria F.; Armbruster, Jonathan W.; Harris, Phillip M.; O’neil, Patrick E. (Zootaxa, 2023)
Checklists are fundamental and important tools for organizing information about biodiversity that provide a basis for conservation and additional scientific research. While Alabama is recognized as an aquatic biodiversity ‘hotspot’ with the highest native freshwater fish diversity in the contiguous United States, we currently lack an up-to-date list of the state’s fishes. In particular, much has changed over the past 20 years regarding our knowledge of fishes from Alabama and the Mobile River Basin, rendering past comprehensive treatments by Mettee et al. (1996) and Boschung and Mayden (2004) out of date. Here, we provide a revised checklist of marine and freshwater fishes known from the coastal and inland waters of Alabama that includes 463 species (335 primarily freshwater fishes, and 128 marine or diadromous fishes) in 35 orders, 78 families, and 176 genera. Extant, extirpated, and extinct species are included, as are putative candidate species. The checklist is based on prior work, searches of the literature and online sources, as well as parsing a large compilation of >140,000 fish records for Alabama and the Mobile River Basin from 37 data providers in the global Fishnet2 database (www.fishnet2.net) and >4000 marine survey records from the SEAMAP database (https://www.gsmfc.org/seamap.php). After editing and quality control checks, the final combined database contained 144,215 collection records, 95% of which were georeferenced. We discuss the species descriptions, nomenclatural changes, and updates to marine species that account for changes to the state list, and we close with a discussion of 13 candidate species forms that remain undescribed, which represent outstanding taxonomic issues in need of further research attention.